The Geology of Jandul Valley, Western Dir. - Kakar, Safdar Khan; Mian, Said Badshah; Khan, Jehanzeb (Journal of Himalayan Earth Sciences, 2024)
The geology of Jandul Valley consists of Palaeozoic metamorphic rocks of amphibolite facies, intruded by Igneous rocks in Jurassic-Cretaceous times. The plutonic rocks consist of an earlier phase of diorites, granodiorites, and granites and an apparently later phase of norites, hornblendites, pyroxenites and peridotites. The Mesozoic magmatism was followed by volcanic activity in the Tertiary times. These, consisting of andesitic and dacitic tuffaceous rocks, are intimately inter-bedded with fossiliferous metasedimentary rocks of phyllite grade. This phase is characterized by the intrusion of porphyry dykes which were probably the main feedes at the time. This was followed by a phase of granite and diorite dyke intrusions. Next quartz and pegmatite veins formed, followed by a final stage of dolerite dyke intrusions. Extensive sporadic copper-mineralization is associated with the volcanism. Structurally, the region is complexly folded and faulted. The main bodies of the intrusive and extrusive rocks seem to be located along a thrust zone. At least three tectonic stages are discernible in the area.